Big Data as a Driving Tool of Digital Transformation - Adusumalli, Harshini Priya (ABC Journal of Advanced Research, 2016)
As a result of this research, it was discovered how Big Data is characterized by the five Vs: Velocity, Volume, Variety, Veracity, and Value; and how Hadoop and other tools, in conjunction with distributed computing capacity, are utilized to meet the needs of Big Data. The research defines the abilities necessary to analyze Big Data, as well as the method of Data Mining and how it generates results, and it also includes recommendations. Physicians may use data science to give the best care possible for their patients, and meteorologists can use it to anticipate the scope of local meteorological occurrences. Data science can even be used to predict natural disasters such as earthquakes and tornadoes. Capturing data is an excellent way for businesses to begin their data science journeys. They can begin evaluating the data as soon as they obtain it. Here are some examples of how people produce data and how corporations such as Netflix, Amazon, United Parcel Service (UPS), Google, and Apple exploit the data generated by their customers and workers. When a Data Science project is completed, the final output should be used to communicate new information and insights gained from the data analysis to important decision-makers.